Reversal of alcohol‐induced effects on response control due to changes in proprioceptive information processing. (11th September 2015) - Stock, Ann‐Kathrin; Mückschel, Moritz; Beste, Christian
Abstract: Recent research has drawn interest to the effects of binge drinking on response selection. However, choosing an appropriate response is a complex endeavor that usually requires us to process and integrate several streams of information. One of them is proprioceptive information about the position of limbs. As to now, it has however remained elusive how binge drinking affects the processing of proprioceptive information during response selection and control in healthy individuals. We investigated this question using neurophysiological (EEG) techniques in a response selection task, where we manipulated proprioceptive information. The results show a reversal of alcohol‐induced effects on response control due to changes in proprioceptive information processing. The most likely explanation for this finding is that proprioceptive information does not seem to be properly integrated in response selection processes during acute alcohol intoxication as found in binge drinking. The neurophysiological data suggest that processes related to the preparation and execution of the motor response, but not upstream processes related to conflict monitoring and spatial attentional orienting, underlie these binge drinking‐dependent modulations. Taken together, the results show that even high doses of alcohol have very specific effects within the cascade of neurophysiological processes underlying response control and the integration of proprioceptive information during this process. Abstract : We investigated whether an acute strong alcohol intoxication alters how proprioceptive information is processed during response selection. Using a Simon task with crossed hand position versus parallel hand position, we found an alcohol‐induced reversal of effects. Specific changes in the neurophysiological data suggest that processes related to the preparation and execution of the motor response underlie these modulations. In short, proprioceptive information does not seem to be properly integrated in response selection processes during acute alcohol intoxication as found in binge drinking.